Open Archival Information System Reference Model pada Rancang Bangun Sistem Informasi Arsip Institusi Pendidikan - Intan Dzikria; Sabrina Vidia Riswana (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
Archive information systems are very important in higher education institutions, to make it easier to manage digital archives. Institutions can take advantage of the benefits of digital archives, such as easy access to information, savings in physical space for storage, and protection of documents from damage or loss. One framework for long-term management, maintenance and storage that is often used in digital archives is the Open Archival Information System (OAIS) Reference Model. This research aims to design and build an educational institutional archival information system with the OAIS reference model that supports long-term access and understanding of information, especially in digital archives. The results of this research are the architectural design of an OAIS-based archive system which can be a reference for developing similar archive systems in educational institutions. The results of system testing using the black-box method, with 95% of functionalities passing the test, show that monitoring and evaluation of archives, especially in terms of long-term storage and identification of archive risks, is following user needs.